High Q, miniaturized dual-mode coaxial bandpass filter - Sovuthy, C. (Institute of Electrical and Electronics Engineers Inc., 2014)
A novel dual-mode coaxial resonator filter based on the stepped-impedance line is introduced in this paper. The theory of dual-mode resonator and its feasibility of higher order realization based on parallel connected network are shown. The cavity prototype has been fabricated to prove the feasibility of this approach. The measured results show the excellent agreement with the theories. In contrast to the conventional combline based single mode filter, the filter is able to achieve at least 60 size reduction for the same Q-factor. Copyright 2014 IEICE.